2013
DOI: 10.1073/pnas.1219502110
|View full text |Cite
|
Sign up to set email alerts
|

Transient protonation changes in channelrhodopsin-2 and their relevance to channel gating

Abstract: The discovery of the light-gated ion channel channelrhodopsin (ChR) set the stage for the novel field of optogenetics, where cellular processes are controlled by light. However, the underlying molecular mechanism of light-induced cation permeation in ChR2 remains unknown. Here, we have traced the structural changes of ChR2 by time-resolved FTIR spectroscopy, complemented by functional electrophysiological measurements. We have resolved the vibrational changes associated with the open states of the channel (P 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
414
3
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(459 citation statements)
references
References 54 publications
(92 reference statements)
36
414
3
5
Order By: Relevance
“…1B (14,40). According to this model, blue light excitation leads to a retinal all-trans to 13-cis isomerization, resulting in a red-shifted first intermediate P 500 1 (12) resembling a K-like state, which most likely contains a 13-cis,15-anti retinal Schiff base chromophore similar to Bacteriorhodopsin (27).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1B (14,40). According to this model, blue light excitation leads to a retinal all-trans to 13-cis isomerization, resulting in a red-shifted first intermediate P 500 1 (12) resembling a K-like state, which most likely contains a 13-cis,15-anti retinal Schiff base chromophore similar to Bacteriorhodopsin (27).…”
mentioning
confidence: 99%
“…A chimera of ChR1 and ChR2 has been crystallized to yield a structure at 2.3-Å resolution (9). However, little is known on how this coupling functions on a molecular level, and a large number of studies based on visible (10-13), IR (11,[14][15][16][17][18][19], resonance Raman spectroscopy (20, 21), and EPR spectroscopy (22, 23) has been performed to address this question.The photocycles of microbial rhodopsins are usually compared with bacteriorhodopsin, the first discovered and most studied lightdriven proton pump (24). Without any illumination, microbial retinal proteins thermally equilibrate into a dark state (25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work on channelrhodopsins CrChR2 and PsChR2 indicated that laser-induced current transients roughly correlate with late photocycle intermediate(s) observed in independent photochemical studies (9,10). The complex time dependence of the current response to step or continuous illumination, however, is difficult to reconcile with the reaction sequence derived from photochemical measurements (9,(11)(12)(13)(14). The desire to explain the unusual * This work was supported by National Institutes of Health Grant R01EY000983 from the NEI (to D. S. K.).…”
Section: Channelrhodopsins (Chrs)mentioning
confidence: 96%